Improving the efficiency of functioning of the bankruptcy institution in the Russian Federation: the value-based approach - E. P. KOCHETKOV (Стратегические решения и риск-менеджмент, 2017)
Today the bankruptcy institution develops dynamically under the influence of various factors. This is required the formation of the universal goals of the bankruptcy institution with considering of features of the current socio-economic development. On the other hand, the transformation purposes of the bankruptcy institution towards rehabilitation focus is not always accompanied by an increase of efficiency of bankruptcy procedures, that confirms by the statistics data in the Russia. Thereby author investigated the issues of determining the universal target installation of bankruptcy institution, as well as an analysis of the bankruptcy models, which confirmed the effectiveness of the bankruptcy models in which decisions on rehabilitation or liquidation of the debtor is based on value criteria. In order to enhance the rehabilitation capacity of the bankruptcy institution in Russia on the basis of a systematic approach author proposed changes in the concept of the impact of the bankruptcy procedures, measures to improve the efficiency of bankruptcy procedures, and explore the essence of the process of restoring the debtor's solvency. It is proved that the purpose of rehabilitation of bankruptcy procedures should be the preservation of the debtor's business with the new owner of more efficient, taking into account interests of society as a whole.